2023
DOI: 10.1021/acs.accounts.3c00394
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and Delivery of cGAS-STING Immunomodulators for the Immunotherapy of Cancer and Autoimmune Diseases

Shurong Zhou,
Furong Cheng,
Yu Zhang
et al.

Abstract: The cyclic GMP-AMP synthase-stimulator interferon gene (cGAS-STING) pathway is an emerging therapeutic target for the prophylaxis and therapy of a variety of diseases, ranging from cancer, infectious diseases, to autoimmune disorders. As a cytosolic double stranded DNA (dsDNA) sensor, cGAS can bind with relatively long dsDNA, resulting in conformational change and activation of cGAS. Activated cGAS catalyzes the conversion of adenosine triphosphate (ATP) and guanosine triphosphate (GTP) into cGAMP, a cyclic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In the context of tumor immunotherapy, it has been reported that activating the cGAS-STING signaling pathway and creating a proinflammatory immune microenvironment are necessary for the response to anti-PD-1 antibody-mediated immunotherapy in vivo [ 5 , 6 ]. cGAS can sense free DNA in the cytoplasm [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of tumor immunotherapy, it has been reported that activating the cGAS-STING signaling pathway and creating a proinflammatory immune microenvironment are necessary for the response to anti-PD-1 antibody-mediated immunotherapy in vivo [ 5 , 6 ]. cGAS can sense free DNA in the cytoplasm [ 7 ].…”
Section: Introductionmentioning
confidence: 99%